2023
DOI: 10.3390/nano13020263
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Heterojunctions Based on Cs3Bi2Br9 Nanocrystals and g-C3N4 Nanosheets for Photocatalytic Hydrogen Evolution

Abstract: Heterojunctions based on metal halide perovskites (MHPs) are promising systems for the photocatalytic hydrogen evolution reaction (HER). In this work, we coupled Cs3Bi2Br9 nanocrystals (NCs), obtained by wet ball milling synthesis, with g-C3N4 nanosheets (NSs), produced by thermal oxidation of bulk g-C3N4, in air. These methods are reproducible, inexpensive and easy to scale up. Heterojunctions with different loadings of Cs3Bi2Br9 NCs were fully characterised and tested for the HER. A relevant improvement of H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It was observed that bulk g-C 3 N 4 and Cs 3 Bi 2 Br 9 absorbed similar wavelengths of light with absorption edges at around 463 and 493 nm, respectively. Measuring the absorbance of the composites in comparison to the pure semiconductors showed a higher absorbance between 300 and 450 nm with a slight redshift for the composites . In particular, the 40 wt % Cs 3 Bi 2 Br 9 /g-C 3 N 4 composite demonstrated the highest light absorbance, suggesting that this composition forms a heterostructure where the two semiconductors complement each other in terms of light harvesting ability, which is important for the photogeneration of charges.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was observed that bulk g-C 3 N 4 and Cs 3 Bi 2 Br 9 absorbed similar wavelengths of light with absorption edges at around 463 and 493 nm, respectively. Measuring the absorbance of the composites in comparison to the pure semiconductors showed a higher absorbance between 300 and 450 nm with a slight redshift for the composites . In particular, the 40 wt % Cs 3 Bi 2 Br 9 /g-C 3 N 4 composite demonstrated the highest light absorbance, suggesting that this composition forms a heterostructure where the two semiconductors complement each other in terms of light harvesting ability, which is important for the photogeneration of charges.…”
Section: Resultsmentioning
confidence: 93%
“…While possessing an alignment in band energetics and complementary optoelectronic properties, research on Cs 3 Bi 2 Br 9 /g-C 3 N 4 composites has been focused on H 2 evolution and oxidation reactions. To date, little research has explored photocatalytic CO 2 reduction in the gas-phase without the use of hole scavengers. In this work, we successfully synthesized a direct Z-scheme heterojunction between Cs 3 Bi 2 Br 9 and bulk g-C 3 N 4 using a straightforward antisolvent crystallization method.…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, bismuth- and antimony-based perovskite derivatives of general formula Cs 3 M 2 X 9 (M = Bi, Sb; X = Br, I) have shown strong technological potential, in particular in the area of photocatalysis (both for solar fuel generation and organic synthesis) and photodetection. 20–36…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, bismuth-and antimony-based perovskite derivatives of general formula Cs 3 M 2 X 9 (M = Bi, Sb; X = Br, I) have shown strong technological potential, in particular in the area of photocatalysis (both for solar fuel generation and organic synthesis) and photodetection. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Bismuth-based defect-ordered perovskites have been an object of more intense studies compared to the corresponding Sb systems, notwithstanding their appealing optoelectronic properties such as high carrier mobility, low trap density, and long diffusion length. As a matter of fact, Cs 3 Sb 2 Br 9 millimetersized single crystals and nanoflakes have been applied in the fabrication of photodetectors with excellent performance in terms of responsivity and detectvity.…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, bismuth-and antimony-based perovskite derivatives of general formula Cs3M2X9 (M=Bi, Sb; X=Br, I) have shown a strong technological potential in particular in the area of photocatalysis (both for solar fuel generation and organic synthesis) and photodetection. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Bismuth-based defect-ordered perovskites have been object of more intense studies with respect to the corresponding Sb systems, notwithstanding their appealing optoelectronic properties such as high carrier mobility, low trap density, and long diffusion length. As a matter of fact, Cs3Sb2Br9 millimeter-sized single crystals and nanoflakes have been applied in the fabrication of photodetectors with excellent performance in terms of responsivity and detectvity.…”
Section: Introductionmentioning
confidence: 99%